2015
DOI: 10.1007/s12298-015-0326-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic diversity among six populations of Gossypium arboreum L. using microsatellites markers

Abstract: Among the four cultivated cotton species, G. hirsutum (allotetraploid) presently holds a primary place in cultivation. Efforts to further improve this primary cotton face the constraints of its narrow genetic base due to repeated selective breeding and hence demands enrichment of diversity in the gene pool. G. arboreum (diploid species) is an invaluable genetic resource with great potential in this direction. Based on the dispersal and domestication in different directions from Indus valley, different races of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The AMOVA results estimated 38% variation among population of accessions and 62% genetic variation within the populations of both species. A similar previous study indicated 14% variation among populations and 52% variation between individuals of G. arboreum [56].…”
Section: Discussionsupporting
confidence: 81%
“…The AMOVA results estimated 38% variation among population of accessions and 62% genetic variation within the populations of both species. A similar previous study indicated 14% variation among populations and 52% variation between individuals of G. arboreum [56].…”
Section: Discussionsupporting
confidence: 81%
“…3-5 However, the high genetic similarity among G hirsutum accessions has hindered opportunities for breeding new cotton cultivars with improved agricultural traits such as higher yield, ease of harvest, and stronger resistance to pest, diseases, and environmental stresses. 6-10…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, the high genetic similarity among G hirsutum accessions has hindered opportunities for breeding new cotton cultivars with improved agricultural traits such as higher yield, ease of harvest, and stronger resistance to pest, diseases, and environmental stresses. [6][7][8][9][10] Seven genetically related accessions of G hirsutum, including Latifolium, Palmeri, Marie-Galante, Richmondi, Yucatanense, Morrilli, and Punctatum, have been identified based on their locations of origin. 11 These races have distinct characteristics that are common to wild cotton but not to cultivated G hirsutum, such as sensitivity to a short-term light cycle, greater disease resistance and drought tolerance, hard seed coats, and variable seed size, and are genetically compatible with domesticated cottons.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluated the genetic diversity of landraces in G. arboreum L. race by using simple sequence repeats (SSRs) (Liu 2007), where the result of these studies revealed a higher level of genetic variation at the DNA level among the G. arboreum accessions than that among G. hirsutum L. accessions. The transition of intraspecific and interspecific hybridization of allelic diversity from different cotton germplasm services to the main cotton breeding gene pools would be an important step in this direction (Sethi et al, 2015). The current study focuses on genetic improvement by using molecular breeding approaches for the production of highly desirable desi cotton verities with traits of interest.…”
Section: Introductionmentioning
confidence: 99%